Quantifying the effect of a cancer diagnosis on Medicare payments and use according to new Public Use Files. (2014)
New public use data sets available from the Centers for Medicare and Medicaid Services include a cancer indicator that allows for interesting comparisons with other chronic conditions among Medicare beneficiaries. When compared with beneficiaries with no chronic conditions, Medicare beneficiaries with a cancer diagnosis and no other chronic condition cost 5 times more and result in 5 times as many inpatient admissions.